A tribute to Gaza - Omer, Spahic (Dar al-Wahi Publication, 2023)
The tragic Gaza events signify a battlefield for clashes between civilization and barbarism, truth and falsehood, sanity and madness, and between humanity and otherwise. Thus, Gaza’s theatre of war is not confined merely to a tiny strip of land wedged between Egypt, the Mediterranean Sea and Israel as an illegal geopolitical entity, but rather extents far and wide to encompass all parts of the planet. Everyone feels compelled to make a stand, both personally and institutionally. In a way – it stands to reason – the Gaza conflict is a global phenomenon; it is a “world war” between discordant worldviews, value systems and existential paradigms.